Revisiting UTAUT in the Digital Finance Era: The Mediating Role of Financial Literacy in Crypto Investment Behavior - Novita Ratna Satiti; Reza Aryo Dwifa (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study is to analyze the effect of Unified Theory of Acceptance and Use of Technology (UTAUT) variables, including Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions, on cryptocurrency investment decisions, with financial literacy serving as a mediating variable. Methodology: This study employs a quantitative method using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Data were collected through an online questionnaire distributed to 254 respondents who actively use cryptocurrency investment platforms in Indonesia. Results: The result of the study reveal that Performance Expectancy, Effort Expectancy, and Social Influence do not significantly affect cryptocurrency investment decisions. In contrast, Facilitating Conditions have a positive and significant indirect effect on investment decisions through financial literacy. Financial literacy also has a role for significant mediating in strengthening the relationship between technology acceptance factors and investment behavior. Conclusions: Financial literacy plays an important role of decisions related to cryptocurrency investment, while facilitating conditions strengthen investment behavior by improving users’ financial understanding. These findings highlight the importance of combining technology acceptance factors with financial capability in explaining cryptocurrency investment behavior. Limitations: This study is limited to respondents in Indonesia and relies on self-reported data collected through an online questionnaire, this condition may reduce the extend to which the findings can be generalized. Contributions: This research contributes to the knowledge in financial technology and digital investment by highlighting the mediation effect of financial literacy on UTAUT variables and cryptocurrency investment decisions.